2017
DOI: 10.14196/mjiri.31.44
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis in rheumatoid arthritis patients, abundance and association with disease activity

Abstract: Background: There are some discrepancy in association between activity of rheumatoid arthritis (RA) and periodontitis. The aim of this study was to evaluate the periodontal status of outpatients with RA. Methods: The study was conducted in 2013-14 in a rheumatology clinic in Sari, north of Iran on 74 patients with RA. Evaluation of RA disease activity was according to disease activity score 28 (DAS28). Periodontitis was evaluated by probing depth (PD), gingival index (GI), clinical attachment level (CAL index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
2
16
0
3
Order By: Relevance
“…In the oral cavity, pathogenic bacteria can form clusters, which in turn leads to inflammation, thereby increasing the number of bacteria in the periodontal pocket. These changes lead to further inflammatory and immune‐mediated tissue changes, further environmental changes and tissue destruction, culminating in a predominance of periodontal pathogens and a greater degree of tissue damage . In this process, P. gingivalis is the most important strain causing periodontal disease and systemic inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the oral cavity, pathogenic bacteria can form clusters, which in turn leads to inflammation, thereby increasing the number of bacteria in the periodontal pocket. These changes lead to further inflammatory and immune‐mediated tissue changes, further environmental changes and tissue destruction, culminating in a predominance of periodontal pathogens and a greater degree of tissue damage . In this process, P. gingivalis is the most important strain causing periodontal disease and systemic inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…These changes lead to further inflammatory and immune-mediated tissue changes, further environmental changes and tissue destruction, culminating in a predominance of periodontal pathogens and a greater degree of tissue damage. 22 In this process, P. gingivalis is the most important strain causing periodontal disease and systemic inflammation. 14 Previous studies have confirmed that P. gingivalis in aortic tissues, including vascular endothelial cells can cause inflammation characteristic of rheumatoid arthritis, arteriosclerosis, and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…La evidencia científica actual establece una asociación entre AR y PC. Específicamente se reporta una mayor prevalencia de PC en pacientes con diagnóstico de AR 19,22 y un mayor riesgo para el desarrollo de AR en pacientes con PC en comparación con la población general 23 . En este contexto, Mikuls et al 19 reportaron 35% de prevalencia de PC en pacientes con AR, mientras que Mobini et al 22 describen 63,5%.…”
Section: Discussionunclassified
“…Similares fueron los resultados de Lee et al 20 y Choi et al 21 , en los cuales la PC moderada fue observada en 61,7% y 61% de los pacientes con AR, respectivamente (p < 0,001). Estos resultados han sido confirmados recientemente en el estudio de Mobini et al 22 , donde 63,5% de los pacientes con AR padecía PC y 12,2% PC moderada-grave, siendo la PC más prevalente en AR en compara-ción con controles. Por otra parte, Chou et al 23 investigaron el riesgo de AR asociado a la exposición a PC en una cohorte compuesta por un millón de participantes seleccionados al azar durante el año 2010 en Taiwán.…”
Section: Datos Epidemiológicos (Tabla 1)unclassified
See 1 more Smart Citation